Electrical and Structural Adaption of Athlete’s Heart and the Impact on Training and Recovery Management in Professional Basketball Players: A Retrospective Observational Study - Zimmermann, Paul; Moser, Othmar; Edelmann, Frank; Schöffl, Volker; Eckstein, Max L.; Braun, Martin (Frontiers in Physiology, 2022)
Introduction We analyzed data of 27 professional basketball players to prove cardiac remodeling referring echocardiographic parameters, cardiopulmonary exercise testing (CPET), and 12-lead electrocardiogram (ECG) analyses. The aim of our study was to present different characteristics in the athletes, on the one hand signs of a high vagal tone in the 12-lead ECG as criteria of early repolarization (ER), furthermore echocardiographic remodeling parameters and finally the performance in CPET. Therefore, we divided the cohort into a group with signs of ER pattern in the 12-lead ECG and without these criteria and presented the differences in detail. Materials and Methods This was a single-center, retrospective study performed in 27 professional basketball players (age: 26.5 ± 7.5 years, male: 27, height: 197.2 ± 12 cm, weight: 100 ± 17 kg, BMI: 25.7 ± 3.4 kg/m2). All participants underwent a sports medicine checkup, ECG analysis, transthoracic echocardiographic examination, and a CPET on a cycle ergometer between 2015 and 2019 during their pre-season preparation time. All individuals were healthy people without cardiological advance anamnesis. After assessment, two groups were built based on electrocardiographic criteria of ER pattern and a group without these criteria and compared against each other for parameters of echocardiographic assessment, CPET, and 12-lead ECG analysis. Data were analyzed with Minitab statistic program (Minitab Inc., State College, PA, United States) and Graph Pad Prism 8.2.1 (279; Graph Pad Software, San Diego, CA, United States) using ANOVA testing with post-hoc testing and unpaired t-testing (p ≤ 0.05). Retrospectively additional information was collected referring to the management of training sessions, recovery time, and nutrition by interviewing the athletic training staff in order to understand the principles for individual athlete’s training management and physiological and cardiopulmonary interactions. Results Comparing professional basketball players with ER pattern to those with no ER pattern, significant differences were found for CPET, echocardiographic, and ECG analysis (p < 0.05). Absolute and relativized peak oxygen uptake (VO2 peak; ER 4120 ± 750 ml/min (39 ± 5.4 ml/kg/min) vs. non-ER 3556 ± 393 ml/min (37.2 ± 5.3 ml/kg/min), p = 0.018) and maximum workload during CPET (ER 310 ± 51.5 Watt (2.94 ± 0.35 W/kg) vs. non-ER 271 ± 32 Watt (2.85 ± 0.49 W/kg), p = 0.026) was higher in athletes with an ER pattern. Furthermore, ER pattern athletes showed a higher enddiastolic left ventricular diameter (LVedd; ER 58.3 ± 7.9 mm vs. non-ER 53.6 ± 3.6 mm, p = 0.048) and a significantly enlarged left atrial (LA) endsystolic diameter (ER 23.33 ± 2.71 mm vs. non-ER 20.47 ± 2.29 mm, p = 0.006) as well as a significantly enlarged right atrial (RA) endsystolic diameter (ER 23.42 ± 2.15 mm vs. non-ER 20.93 ± 3.28 mm, p = 0.033). Significant differences between the two compared groups could be revealed for left ventricular mass Index (LVMI gr/m2; LVMI ER 113 gr/m2 ± 17.5 vs. LVMI non-ER 91.3 gr/m2 ± 15.1, p = 0.002), but no significant differences for the relative wall thickness were found (RWT; RWT ER 0.49 ± 0.11 vs. RWT non-ER 0.38 ± 0.06, p = 0.614). Conclusion Professional basketball players with criteria of ER pattern showed different results in CPET and cardiac remodeling as athletes with no ER pattern. These findings should encourage the athletic training staff to emphasize the quality of an individual training schedule for each athlete based on the cardiopulmonary pre-season sport medicine checkup. Nevertheless, echocardiographic findings, ER pattern, and performance in CPET have to be interpreted referring the sport-specific and athlete’s ethnical background.